For the following exercises, evaluate the function f at the values f(−2), f(−1), f(0), f(1), and f(2)

70. f(x) = 8x2 − 7x + 3

Respuesta :

Answer:

See below.  I assume that (x) = 8x2 - 7x + 3 is really (x) = 8x^2 - 7x + 3

Step-by-step explanation:

Substitute the value of x given in f(x) into the equation f(x) = 8x^2 - 7x + 3

For example, f(0) would be f(0) = 8(0)^2 - 7(0) + 3.  f(0) = 3

f(-2) would be f(-2) = 8(-2)^2 - 7(-2) + 3.  

                                =   8*4  + 14 +3

                                = 32 + 17        therefore      f(-2) = 49

x f(x)

-2 49

-1 18

0 3

1 4

2 21